Queuing with adaptive modulation and coding over wireless links: cross-Layer analysis and design - Qingwen Liu; Shengli Zhou; Giannakis, G.B. (IEEE transactions on wireless communications, 2005)
Assuming there are always sufficient data waiting to be transmitted, adaptive modulation and coding (AMC) schemes at the physical layer have been traditionally designed separately from higher layers. However, this assumption is not always valid when queuing effects are taken into account at the data link layer. In this paper, we analyze the joint effects of finite-length queuing and AMC for transmissions over wireless links. We present a general analytical procedure, and derive the packet loss rate, the average throughput, and the average spectral efficiency (ASE) of AMC. Guided by our performance analysis, we introduce a cross-layer design, which optimizes the target packet error rate of AMC at the physical layer, to minimize thpacket loss rate and maximize the average throughput, when combined with a finite-length queue at the data link layer. Numerical results illustrate the dependence of system performance on various parameters, and quantify the performance gain due to cross-layer optimization. Our focus is on the single user case, but we also discuss briefly possible applications to multiuser scenarios.